Childhood Septicemia in Nepal: Documenting the Bacterial Etiology and Its Susceptibility to Antibiotics. (25th December 2014) - Ansari, Shamshul; Nepal, Hari Prasad; Gautam, Rajendra; Shrestha, Sony; Neopane, Puja; Rimal, Brihaspati; Mandal, Fuleshwar; Ansari, Safiur Rahman; Chapagain, Moti Lal
Abstract : Introduction . Children are among the most vulnerable population groups to contract illnesses. The varying microbiological pattern of septicemia warrants the need for an ongoing review of the causative organisms and their antimicrobial susceptibility pattern. Therefore, the objective of this study was to document the bacterial etiology of childhood septicemia and its antibiotic susceptibility profile. Methods. Cross-sectional type of study in 1630 suspected patients was conducted at CMCTH from January 2012 to December 2013. Blood samples were collected aseptically for culture. The organisms grown were identified by standard microbiological methods recommended by American Society for Microbiology (ASM) and subjected to antibiotic susceptibility testing by modified Kirby-Bauer disk diffusion method. Methicillin resistance was confirmed using cefoxitin and oxacillin disks methods. Results. Septicemia was detected in 172 (10.6%) cases. Among Gram-positive organisms, coagulase negative staphylococci (CoNS) were leading pathogen and Acinetobacter spp. were leading pathogen among Gram-negative isolates. Vancomycin, teicoplanin, and clindamycin were the most effective antibiotics against Gram-positive isolates while amikacin was effective against Gram-positive as well as Gram-negative isolates. Methicillin resistance was detected in 44.4% of Staphylococcus aureus . Conclusions . This study has highlighted the burden of bacterial etiology for septicemia among children in a tertiary care center of central Nepal.